How Is Bark Absorbability and Wettability Related to Stemflow Yield? Observations From Isolated Trees in the Brazilian Cerrado - Tonello, Kelly Cristina; Campos, Sergio Dias; de Menezes, Aparecido Junior; Bramorski, Julieta; Mathias, Samir Leite; Lima, Marcelle Teodoro (Frontiers in Forests and Global Change, 2021)
Few investigations have examined the structural controls of bark on its water storage and influence on stemflow, despite the bark being considered a critical component that determines the time and magnitude of this process. This study seeks to answer the question: Do bark water absorbability and wettability estimates correlate with stemflow yield? We hypothesized that (1) the absorbability and wettability are correlated, that is, greater water absorbability implies greater wettability, and (2) high rates of bark water absorbability and wettability has a strong and negative correlation with stemflow generation. Stemflow yield (Sy) was monitored over 12 months for 31 trees, representing 9 species common to the Brazilian savanna ecosystem known as Cerrado. Bark absorbability, per unit dry weight, changes over time of the water absorbability (BWA - by submersion methodology), bark drying (BWD), bark absorbability rate (BWArate), bark drying rate (BWDrate), and wettability (initial contact angle – CAin and CA rate - CArate) were determined under laboratory conditions. As insoluble lignin may also act to alter bark water storage dynamics, for each species, the bark insoluble lignin content was characterized. Stemflow variability was significant across the study species. Funneling ratios (FR) indicates that all species’ canopies diverted enough rainfall as stemflow to concentrate rainwaters at the surface around their stem bases (FR > 1). Differences in bark water absorbability were notable some of tree species. A decrease in the CA value as a function of time was not observed for all barks, which in association with stemflow yields, allowed a novel classification method of wettability, based on CAin and it’s rate of change: highly wettable (CAin ≤ 75.3° and CArate ≥ 0.26°h–1) and non-wettable (CAin ≥ 93.5° and CArate ≤ 0.13°h–1). So, only from the wettability classification could be observed that the non-wettable bark species presented higher Sy, FR, BWA, and BWArate than highly wettable bark species. The stemflow from species with highly wettable bark had a strong and positive correlation with BWA. On the other hand, non-wettable bark stemflow yield has a strongly and negative correlation with FR, CAin, and BWArate. Thus, bark wettability properties showed to deserves special attention. This novel classification of bark wettability had a substantial effect on stemflow yield comprehension and proved to be an important variable to link laboratory and field investigation for understanding the stemflow yield. These findings will improve our understanding of the stemflow dynamics, water balance and the ecohydrology processes of forest ecosystems.